2017
DOI: 10.1038/s41598-017-14798-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil hypoxia induced by an organic-material mulching technique stimulates the bamboo rhizome up-floating of Phyllostachys praecox

Abstract: Phyllostachys praecox bamboo stands significantly recede after 3 or 4 years using an organic-material mulching technique consecutively. We hypothesized that the bamboo recession is caused by the up-floating of underground rhizome stimulated by soil hypoxia through the mulching technique. This study aimed to validate this hypothesis by field investigation. Bamboo underground rhizome distribution in the soil profile of P. praecox subjected to various mulching times was investigated. Results showed that bamboo rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…In this study, it was found that mulching cultivation associated with highly intensive management caused the bamboo bud bank to rise obviously in the soil; the longer the mulching time, the smaller the total bud number, the greater the bud mortality numbers, and the weaker the bud-input and bud-output ability. The residual mulching materials of bamboo forests easily produce fertilizing effects after mineralization, and bamboo rhizome has a strong tropism towards fertile soil (Xu et al 2017), which should be an important reason for the rising of bamboo bud bank. Therefore, residual mulching materials should be cleaned with time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was found that mulching cultivation associated with highly intensive management caused the bamboo bud bank to rise obviously in the soil; the longer the mulching time, the smaller the total bud number, the greater the bud mortality numbers, and the weaker the bud-input and bud-output ability. The residual mulching materials of bamboo forests easily produce fertilizing effects after mineralization, and bamboo rhizome has a strong tropism towards fertile soil (Xu et al 2017), which should be an important reason for the rising of bamboo bud bank. Therefore, residual mulching materials should be cleaned with time.…”
Section: Resultsmentioning
confidence: 99%
“…In bamboo forests, mulching of the shoot has produced great economic benefits, but the bamboo plant is severely stressed by human disturbance, which seriously affects the physiological activities of bamboo (Xu et al 2017). Phyllostachys praecox Z. D. Chu et C. S. Chao 'Prevernalis' S. Y. Chen et C.Y.…”
Section: Introductionmentioning
confidence: 99%
“…Moso bamboo shoots are rich in fiber and nutrients, making them a desirable health food with increasing demand 1,2 . The income from bamboo shoot business has reached $30,000 per hectare in advanced cultivation areas 3 . Techniques to improve shoot production rely mainly on fertilization management 4–9 .…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia is a serious impeding factor for plant growth, and results in signi cant yield losses (Bailey-Serres and Voesenek 2008). Hypoxia mainly includes ooded hypoxia and non-ooded hypoxia, such as soil compaction and mulching (Xu et al 2017). Plants are obligate aerobes, requiring oxygen for mitochondrial respiration and energy production.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely promoted and cultivated in most Southern provinces of China (An et al 1994). Previous studies have shown that the bamboo rhizomes of P. praecox often suffered soil hypoxia with mulching cultivation (Xu et al 2017). P. praecox is susceptible to ooding in the wild environment.…”
Section: Introductionmentioning
confidence: 99%